How do Students Deal with Socio-scientific Issues: A Development of Students' Decision-Making Skills Instrument - Utami, Restu; Prodjosantoso, Anti Kolonial; Rohaeti, Eli; Kamari, Azlan (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2024)
Decision-making skills is needed in dealing with socio-scientific issues (SSI) that is developing in society. Students need to learn to make appropriate judgments, so that they were not easily manipulated or biased towards science-related issue. This paper aims to analyze the validity and reliability of the decision-making skills instrument. The research respondents were 75 high school students (female = 52, male = 23) at Bantul Regency, Special Region of Yogyakarta. The decision-making skills instrument consists of 5 items open-ended questionnaire. Respondents were determined using the random sampling method. The validity test results showed that all of 5 items developed were valid, with Pearson product moment values between 0.572 and 0.801. The reliability test results were valid for all 5 items, with a Cronbach's Alpha coefficient of 0.744. Therefore, it could be concluded that the instrument was valid and highly reliable to measure students' decision-making skills.